Finite element analysis of disc brake squeal - Wan Mohd. Musyris Wan Harujan, author; Abd. Rahim Abu Bakar, author; Badri Abdul Ghani, author; International Conference on Recent and Emerging Advanced Technologies in Engineering (2009 : Selangor) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL